Marketplace Promotion as a Moderating Variable in the Effect of Shopee PayLater Usage on Purchasing Decisions of Students of the Faculty of Economics, Gunung Rinjani University - Halimatussya'diyah, Halimatussya'diyah; Hidayat, Ahmad (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study aims to analyze the effect of Shopee PayLater usage on students’ purchasing decisions and to examine the role of marketplace promotions as a moderating variable. This research employs a quantitative approach with an explanatory research method. The sample consists of 61 respondents selected from a population of 159 students of the Faculty of Economics at Gunung Rinjani University using the Slovin formula. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that Shopee PayLater usage has a positive effect on students’ purchasing decisions. Marketplace promotions are also found to have a direct positive effect on purchasing decisions. However, the interaction test results show that marketplace promotions do not act as a moderating variable in the relationship between Shopee PayLater usage and students’ purchasing decisions. These findings suggest that although digital payment convenience and promotions both influence purchasing decisions, they operate independently and do not strengthen each other through interaction effects.